Localization of Five Antibiotic Resistances at the Subunit Level in Chloroplast Ribosomes of Chlamydomonas - Schlanger, Gladys (Proc Natl Acad Sci U S A, 1974)
The chloroplast ribosomes from five antibiotic resistant strains of Chlamydomonas, each carrying one mutant gene mapping in chloroplast DNA, have been shown to be resistant to the corresponding antibiotic in a poly(U)-directed amino-acid incorporating assay system. The alteration conferring resistance was localized to the 30S subunit in ribosomes from streptomycin, neamine, and spectinomycin resistant strains, and to the 50S subunit in ribosomes from cleocin and carbomycin resistant strains. Spectinomycin resistant ribosomes showed no cross-resistance to any other drugs, but limited cross-resistance was noted with the other mutant ribosomes. The similarity between these findings and results reported by others with bacterial ribosomes supports our hypothesis that at least some chloroplast ribosomal proteins are coded by genes in chloroplast DNA. IMAGES: